Anal squamous cell carcinoma: are we improving outcomes?. Issue 10 (29th August 2018) - Mackowski, Alicia; Levitt, Michael; Makin, Gregory; Salama, Paul; Tan, Patrick; Penter, Cheryl; Platell, Cameron
Abstract : Background: Anal squamous cell carcinoma (SCC) is a rare malignancy. The purpose of this study was to review a single institution's experience. Methods: All patients with anal SCC from St John of God Subiaco Hospital database were identified over a 10‐year period (2006–2016). Patients with stage 1 anal verge tumours underwent wide local excision, all remaining patients were offered chemoradiation (CRT) as an initial treatment modality (a fluorouracil‐based regimen in conjunction with mitomycin). Outcomes included recurrence, overall survival and survival following salvage surgery. Results: Forty‐seven patients were identified. Median age was 60 years and median follow‐up was 2.73 years. Five‐year rates of recurrence and overall survival were 35.8% (95% confidence interval (CI) 23.2–52.4%) and 65.4% (95% CI 47.0–78.7%), respectively. Locoregional failure occurred most commonly at the primary site. Eight patients underwent salvage abdominoperineal resection for persistent or recurrent disease, and four of these patients died within 5 years. Conclusion: CRT is a proven and reasonable effective approach in managing anal cancer. Observed recurrence and overall survival rates in this study resemble the published data. Despite newer methods of treatment being investigated, the treatment for anal SCC has not significantly changed in the past four decades and novel approaches are needed to further improve outcomes.